MAIN CLIMATICS ELEMENTS VARIABILITY AND URBANIZATION IN PIRACICABA´S REGION - COLTRI, PRISCILA P.; FAGNANI, MARIA ANGELA; LABAKI, LUCILA C.; FERREIRA, NELSON J.; DEMÉTRIO, VALDEMAR A. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Climate changes analysis are usually performed by monitoring the climate elements forlong periods of time, enabling the visualization of directional or periodical regional changes.In the current study we studied the climate changes in Piracicaba, SP. The main climateelements were studied using data from ESALQ meteorological station for the last 54 years(1950-2004). Temperature, relative humidity, evaporation and precipitation variation werefound to be correlated with urban growth parameters such as urban and agriculturalpopulation, number of quarters and vegetal covering for inhabitant. The results indicatedthat temperature, precipitation, relative humidity and evaporation increased during thestudied period and have been classified as "climate trends" in accordance with the OMMdefinitions. However, it is not possible to conclude that there was a climatic change. Thetemperature presented the greatest increase and it was positively correlated with urbangrowth. This indicates that urbanization may be the responsible for temperature increaseover the studied years.